PRELIMINARYS TUDY OF THE UTILIZATIONOF THE FLY ASH FROM COAL-FIRED POWER PLANT FOR IMMOBILIZATION OF RADIOACTIVE WASTE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Preliminary study of the utilization of the fly ash from coal-fired power plant for immobilizing simulated radioactive waste has been done. The objective of this research was to study characteristicsof pozzolanic material of the fly ash from coal-fired power plant as substitute of compactor material for immobilizingsimulated radioactive waste. The experiment was carried out by mixing of the compactor materials such as (cement + lime), (cement + fly ash), (cement + fly ash + lime), (fly ash + lime) with Na&#8322